Hemodynamic and analgesic effect of intrathecal dexmedetomidine with low dose hyperbaric bupivacaine in spinal anaesthesia, caesarean section: a randomized controlled trial - Plabon Hazarika; Tapan Kumar Talukdar; Jagadish Basumatary; Dilip Kumar Saloi (New Indian Journal of OBGYN, 2023)
Objectives: Hypotension is the major side effect of spinal anaesthesia during caesarean section. Since the adverse effects are dosage-dependent, various methods have been tried to prevent spinal anaesthesia induced complications, such as lowering the local anaesthetic dose and combining it with additives like neuraxial opioids, alpha-2 agonist e.g. dexmedetomidine. Here we are investigating the efficacy dexmedetomidine with hyperbaric bupivacaine for improved postoperative analgesia and more stable hemodynamic during caesarean section. Methodology: An institutional-based RCT was conducted on 60 patients randomly allocated in two groups. Low dose hyperbaric bupivacaine L-DG group (n=30) received 7.5 mg hyperbaric bupivacaine with 5µgm dexmedetomidine and control group S-CG (n=30) received standard dose of hyperbaric bupivacaine of 12.5mg. The hemodynamic parameters, postoperative analgesia, other adverse effects and neonatal outcomes were monitored. Result: The L-DG group had significantly more rapid and persistent sensory block (p < 0.05), stable maternal hemodynamic which was maintained by fewer IV fluids (p < 0.01), lower vasopressor dosages (p < 0.01), no evidence of foetal distress, and a lower incidence of postoperative maternal shivering. Post operative duration of analgesia in L-DG group was more significant (p < 0.001). Conclusion: L-DG group shows stable maternal hemodynamic with fewer demands for vasopressors and fluids, effective sensory blockade and excellent postoperative analgesia.